Using simulations to meld didactic and constructivist teaching methods in complex second year STEM courses - Costabile, Maurizio; Birbeck, David; Aitchison, Claire (International journal of science education, 2025)
This paper explores the effective development and use of interactive simulations as a learning tool, integrating didactic and active approaches with complex laboratory and lecture content in undergraduate biochemistry and immunology courses. University science courses require students to master vast quantities of foundational knowledge that is commonly taught using didactic approaches. Over time, students are required to become more active and teaching approaches become more student-centred, extending students' application of knowledge, critical thinking, and creativity which relies on a student's ability to recall knowledge. Identifying the right timing and means for shifting from didactic approaches toward an active approach is critical for maintaining student interest and extending their learning. Active learning can transform the perception of a given subject, phenomenon, or experience, allowing students to engage meaningfully and deeply with critical and complex ideas. This paper demonstrates how active approaches to learning through simulations have been effectively used to reinforce threshold concepts in laboratory and lecture settings and the impact on student learning is discussed.